Sistem Informasi Pendataan Data Warga di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Nabire - Andre Duma; Ester Ayuk Pusvita; Christian Paul Raymond; Kristia Yuliawan (Jurnal Teknologi dan Informatika, 2023)
The information system for citizen data collection at the Nabire Regency Population and Civil Registration Office plays a critical role in efficiently managing the information of citizens in the region. The system streamlines the data collection, storage, and retrieval processes, ensuring data accuracy and completeness. The information collected through this system can be used for various purposes such as demographic analysis, population studies, and decision-making processes, providing insight to support the betterment of the community. The implementation of this system in the office helps to address the challenges faced in managing the large volume of citizen data. This system is designed to support the efforts of the Population and Civil Registration Office in providing quality services to citizens, and ensuring that their personal information is accurately recorded and maintained. The system provides a comprehensive view of the demographic data, enabling the office to make informed decisions and implement effective policies.